Desenho universal para aprendizagem e acessibilização: pesquisa ação colaborativa na formação de equipe escolar - Romano, Soraia (2023)
Universal Design for Learning is an effective tool to enhance methods, resources, strategies and means of evaluation to facilitate the learning of all students. Schooling in diversity, here is defended as the differences present in all students to participate and learn. And thus, propagates in an incessant search for the promotion of innovative practices and in a process of transformation to make the curriculum accessible to all. The promotion of breaking down barriers in different learning spaces and flexibility, as to the ways of learning and valuing the potentiality of different students, is not yet legitimate. Based on the innovations pointed out by the literature on Universal Design for Learning, the purpose of this study is to develop, implement and evaluate a teacher training program subsidized by the DUA Principles and Guidelines with the research question about how training can contribute to the development of classes based on principles and guidelines that meet the needs of participation of all students to promote learning. As a methodology, we chose collaborative action research to constitute the training of different education professionals in reference to theory and, at the same time, collaborate for the implementation of classes focused on eight classes from 1st to 3rd year of elementary school. The study included 37 students, teachers of regular basic education, special education teachers, educational managers and professionals from the multidisciplinary team. For the data collection, different instruments were used, among them: participants' characterization sheet, class plans formulated collaboratively, lesson planning sheet, photos and videos of innovative classes, Evaluation sheet of the Training Programme and evaluation roadmap for the focus group. The training program was conducted in three meetings of three hours duration and use of different types of materials to motivate participants and obtain different forms of representation. The research had its data found submitted to content analysis with triangulation of different sources. As results, we found the adherence to the training plan implemented and classes planned based on the principles of DUA, which highlighted the use of multiple forms, especially in the principles of engagement and action and expression of different students. The principle of representation had greater resistance and the limits of the research are the lack of opportunity for the continuity of the didactic sequence and the monitoring in the medium and long term. The program was evaluated by all participants through questions with satisfaction scale and open questions for participants. It is concluded that the collaborative proposal in all educational processes present in the classroom and the school accessibility action are important for the different teams working in the school. Finally, it is directed that, for the effectiveness of the DUA in a short period, other research should be favored to apply medium and long term, as a way to ennoble scientific evidence for all modalities of teaching.